Respuesta :

Scryt
One thing before we start :)

AS you can see both numbers after equation have to be negative, 
also we know that 2 same numbers have to add up to -12 and those 2 number after multiplication have to be equal -28

Some theory:

We know that any number which is not negative multiplied by negative will result in negative result, to make it more clear 

[tex](+)*(-)=(-)[/tex]

but

[tex](-)*(-)=(+)[/tex]

we have 2 unknown numbers, let's say it's [tex]x[/tex] and [tex]y[/tex]

[tex]x+y=-12[/tex]
[tex]x*y=-28[/tex]

for [tex]x=2[/tex]
for [tex]y=-14[/tex]

[tex]2+(-14)=2-14=-12[/tex]
[tex](2)*(-14)=-28[/tex]

So your answer is 2 and -14 ;)